Une arme à double tranchant : le déploiement du portrait de la reine dans les édifices gouvernementaux et dans les caricatures québécoises - Desforges, Josée (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2015)
Since the recent increase in the number of representations of Queen Elizabeth II in Canadian government buildings, Quebec cartoonists have seized the motif of the royal portrait to denounce the Harper government’s uses of the sovereign’s image. Drawing on Louis Marin’s definition of representation, this article considers the powers granted by the state to the Queen’s portrait and highlights its critique in Quebec caricatures. Indeed, while the portrait of the Queen allows the Prime Minister to legitimize his authority, its satirical representations denounce the government’s re-actualization of an absent monarchy. The royal portrait is then satirized both as a powerless object and as a weapon threatening to overshadow other Canadian political and religious symbols.